DETERMINING FLOOD MITIGATION MEASURES IN SELECTED LOCAL GOVERNMENT AREAS IN ANAMBRA STATE - Emmanuel Agulue; Ifeanyi C. Enete; Samuel O. Iheukwumere; Joseph O. Duluora (Universitas Negeri Malang, 2025)
This study was driven by the need to determine flood mitigation measures already adopted by the five selected local Government Areas of Anambra State which have had persistent flood incidence. It is hoped that findings of this research will help to improve on the areas where mitigation measures are inadequate. Purposive sampling technique was used in selecting the study area, and simple random sampling technique was used to select the respondents. In all, a total of 392 out of 400 structured questionnaires administered for data collection were retrieved. Analysis of the responses revealed that public education and early flood warning on overall mean responses of 3.33 was highest. Subsequently, overall mean responses on flood warning being issued by government before any flood incidence was seen on 3.31; enforcement of environmental sanitation law was seen on 3.27; enforcement of periodic sanitation was seen on 3,23; clearing of drainages and water ways was seen on 2.92; construction of drainages by the government war seen on 2.67; and construction of drainages through community effort was seen on 2.50. Analysis of responses also revealed that poor flood mitigation measures on the area of construction of artificial levees; building of dams; and afforestation of waterways. Their overall mean responses are 2.14; 2.22; and 2.32 respectively. The research therefore recommended among others that intensive agro forestry along major drainage networks to regulate river flooding, and within fast developing areas to minimize incidence of surface runoff that is associated to increasing paved surfaces. Additionally, it recommended construction of dams at the upper catchment in the basin, and artificial levees to regulate excess water and floods during heavy rains. It also recommended regular clearing of existing water ways as well as construction of more drainage channels to enable easier and freer water flow within their channels.